1999
DOI: 10.1177/135245859900500506
|View full text |Cite
|
Sign up to set email alerts
|

Increased urinary nitric oxide metabolites in patients with multiple sclerosis correlates with early and relapsing disease

Abstract: Nitric oxide (NO) has been implicated in the immunopathogenesis of MS as a potential mediator of neuronal loss. To investigate the role of.NO in the development of progressive disease we measured the NO metabolites (nitrate and nitrite) and neopterin, in the urine of 129 patients with demyelinating disease (DD): 23 with clinically isolated syndromes compatible with demyelination and in 46 relapsing remitting (RR) and 60 patients with progressive MS. Eighty-nine of these 129 patients underwent Gd-enhanced MRI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…These data suggest that in the short-term (9 to 18 months) increased serum NO metabolites may be associated with a better clinical outcome in the form of a non-progressive clinical course and fewer clinical relapses. This finding is corroborated by a large cross-sectional study in which the urinary excretion of NO x was significantly higher in patients with clinically isolated syndromes compatible with demyelination and patients with relapsing remitting MS than in patients with progressive disease [15].…”
Section: Discussionmentioning
confidence: 62%
“…These data suggest that in the short-term (9 to 18 months) increased serum NO metabolites may be associated with a better clinical outcome in the form of a non-progressive clinical course and fewer clinical relapses. This finding is corroborated by a large cross-sectional study in which the urinary excretion of NO x was significantly higher in patients with clinically isolated syndromes compatible with demyelination and patients with relapsing remitting MS than in patients with progressive disease [15].…”
Section: Discussionmentioning
confidence: 62%
“…4 It has been reported that acute axonal damage in MS correlated with inflammatory markers and was most extensive in early disease with gradual decrease over time. 29 In that context, the finding of higher CSF NOx levels in patients with milder disability and less severe disease course compared with those with advanced disease is interesting and seems to indicate the predominant involvement of NO in the early phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…4 Particularly, the intrathecal NOx production was prominent in acute relapse, [5][6][7] but raised CSF NOx concentrations were also reported in progressive disease. 8 Although these studies implicate NO in the pathogenesis of MS, the pathologic events related to elevation of NOx are not fully understood.…”
mentioning
confidence: 97%
“…Urine samples were collected on each visit for clinical evaluation at 0 (baseline), 3,6,9,12,15,18,21,24 months. Urine specimens were collected on different days after injection of IFNb.…”
Section: Biological Sample Collectionmentioning
confidence: 99%
“…serum23 and urine24 in patients with different clinical types of MS suggest that NOx may be an indicator of an ongoing inflammatory process. It has previously been demonstrated that progressive patients Urinary neopterin/creatinine (UNCR) mean values (mmol/mol) in IFNb-1a treated patients with disease progression (o, n ¼ 15) or without disease progression («, n ¼ 14) as assessed on Expanded Disability Status Scale over 2-year followup based on intention-to-treat analysis using Mann-WhitneyWilcoxon test (*p ¼ 0.002; U ¼ 38.0).…”
mentioning
confidence: 98%